The Effect of Urbanization on Community Social Networks and Support Systems - Bandile, Andie (International Journal of Humanity and Social Sciences, 2024)
Purpose: The general objective of this study was to investigate the effect of urbanization on community social networks and support systems. Methodology: The study adopted a desktop research methodology. Desk research refers to secondary data or that which can be collected without fieldwork. Desk research is basically involved in collecting data from existing resources hence it is often considered a low cost technique as compared to field research, as the main cost is involved in executive’s time, telephone charges and directories. Thus, the study relied on already published studies, reports and statistics. This secondary data was easily accessed through the online journals and library. Findings: The findings reveal that there exists a contextual and methodological gap relating to the effect of urbanization on community social networks and support systems. Preliminary empirical review revealed that urbanization significantly fragmented traditional social networks, leading to isolation and reduced informal support systems. However, it also identified opportunities for developing formal support mechanisms through government services, NGOs, and community-based initiatives, enhanced by technology. The study emphasized the importance of inclusive urban policies and thoughtful design to foster social cohesion, suggesting that intentional planning could build resilient and supportive urban communities, ultimately improving residents' quality of life. Unique Contribution to Theory, Practice and Policy: Social Capital Theory, Systems Theory and Social Network Theory may be used to anchor future studies on the effect of urbanization on community social networks and support systems. The study recommended integrating social capital, systems, and social network theories into urban studies, prioritizing the creation of communal spaces, and implementing community-based programs to foster social ties. It advocated for policies ensuring equitable access to social infrastructure, preserving cultural practices, and leveraging technology to enhance social connectivity and support services. Additionally, it emphasized building resilient and inclusive communities, addressing social inequalities, and adopting a holistic approach to urban development to mitigate the negative impacts of rapid urbanization.